Ocean-atmosphere analysis of Super Typhoon Songda 2011 over Western North Pacific Ocean - Yopi Ilhamsyah; Ahmad Bey; Edvin Aldrian; Junaidi M. Affan (Syiah Kuala University, 2013)
The purpose of the research is to understand the influences of ocean and atmosphere to the formation of Super Typhoon Songda 2011. Daily SST from NOAA AVHRR with spatial resolution of 0.5° in latitude and longitude was used to study upper oceanic response to the formation of Typhoon Songda. Meanwhile, 3-hourly meteorological data from ARP model with spatial coverage of 0.5° Latitude x 0.5° Longitude cover 201 x 101 points from 25° N - 20° S and 70.0° E – 170.0° E as well as 13 levels of atmospheric columns was also used in the study. The study was also supported by MT-SAT satellite images. The result showed that from early disturbances until reaching mature stage of Typhoon Songda, SST over WNP reached averages temperature of 30˚C. Warm ocean waters continuously produce heat and moisture to the air that are necessary to fuel the genesis, development, formation and intensification of Typhoon Songda. The study also proved that light vertical wind shear (850 – 200 hPa) at about 0 – 5 knot was observed in the early development of Songda at 1800 UTC on May 19th. For the time being, weak vertical wind shear extended to the northwestern of Pacific Ocean. Thus, it made the system to moved toward northwest and reached category Super Typhoon few days later on May 26th. The study also showed the present of Monsoon trough. Monsoon trough occurred where easterly wind met the reversal southerly wind. The region was stretched from southeast to northwest part of WNP Ocean and designated by an extended low pressure area at the surface as well as extended bands of thunderstorms as observed by satellite imagery. On the other hand, potential vorticity shown in the present paper is useful to obtain an understanding of atmospheric motions and development of the upper-level disturbance. Potential vorticity maximum characterize strong vorticity and upward motion. Conversely, weak vorticity with downward motion is demonstrated by mininum potential vorticity.